Corn bracts loading copper sulfide for rapid adsorption of Hg(II) and sequential efficient reuse as a photocatalyst - Jiwei Wang (IWA Publishing, 2021)
Hg(II) ions in wastewater are highly toxic to the environment and human health, yet many materials to remove the ions exhibit lower adsorption efficiency, and few studies report the reuse of Hg(II)-loaded waste materials. Here, a cheap and efficient adsorbent was prepared for the removal of Hg(II) based on corn bracts (CB) loading copper sulfide (CuS), and the Hg(II)-adsorbed material was reused as a photocatalyst. By changing the adsorption variables such as pH, adsorbent dosage, Hg(II) concentration, contact time and coexisting ions, the optimum adsorption conditions were obtained. The study indicated the adsorption capacity and removal rate of CB/CuS reached 249.58 mg/g and 99.83% at pH 6 with 20 mg CB/CuS, 50 mL Hg(II) concentration (100 mg/L) and 60 min, and coexisting ions did not affect the uptake of Hg(II). The adsorption behavior of CB/CuS toward Hg(II) followed pseudo-second-order and Langmuir models, with the theoretical maximum adsorption capacity of 316.46 mg/g. Finally, we explored an alternative strategy to dispose of spent adsorbents by converting the CB/CuS/HgS into a photocatalyst for the degradation of rhodamine B, with a removal rate of 98%. Overall, this work not only develops a promising material for the treatment of Hg(II)-containing wastewater, but opens up a new approach for the use of the waste adsorbent. HIGHLIGHTS Corn bracts as a carrier of CuS was designed for rapid uptake of Hg(II).; The removal rate of the adsorbent could reach 99.83% in only 60 min.; The theoretical maximum could reach 316.46 mg/g.; Coexisting ions had no significant effect on selective Hg(II) ion removal.; The spent adsorbent was used for photodegradation reaction.;